2019
DOI: 10.1002/jbm.b.34341
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the relative roles of matrix metalloproteinase‐ and plasmin‐mediated matrix degradation during capillary morphogenesis using engineered hydrogels

Abstract: Extracellular matrix (ECM) remodeling is essential for the process of capillary morphogenesis. Here we employed synthetic poly(ethylene glycol) (PEG) hydrogels engineered with proteolytic specificity to either matrix metalloproteinases (MMPs), plasmin, or both to investigate the relative contributions of MMP‐ and plasmin‐mediated ECM remodeling to vessel formation in a 3D‐model of capillary self‐assembly analogous to vasculogenesis. We first demonstrated a role for both MMP‐ and plasmin‐mediated mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…While multiple studies have demonstrated the safety and cellbased formation of vasculature by UV crosslinked hydrogels (Beamish et al, 2019;Chen et al, 2012;Moon et al, 2010), we carefully examined and compared the cytotoxicity of D-hydrogels and N-hydrogels to eliminate the possible impact on ECFCs. No significant change in cell viability was observed in samples treated with various gelation precursors of D-and (F and G) Significant increase in stress relaxation time over 3 days in culture in EGM-2 (F) but half-stress relaxation time, t 1/2 , is maintained lower than in N-hydrogel along the 3-day culture period (G).…”
Section: Hydrogels With Dynamic Network Promote Rapid Vascular Morphogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…While multiple studies have demonstrated the safety and cellbased formation of vasculature by UV crosslinked hydrogels (Beamish et al, 2019;Chen et al, 2012;Moon et al, 2010), we carefully examined and compared the cytotoxicity of D-hydrogels and N-hydrogels to eliminate the possible impact on ECFCs. No significant change in cell viability was observed in samples treated with various gelation precursors of D-and (F and G) Significant increase in stress relaxation time over 3 days in culture in EGM-2 (F) but half-stress relaxation time, t 1/2 , is maintained lower than in N-hydrogel along the 3-day culture period (G).…”
Section: Hydrogels With Dynamic Network Promote Rapid Vascular Morphogenesismentioning
confidence: 99%
“…For example, Moon et al (2010) developed protease-sensitive poly(ethylene glycol) (PEG) hydrogels with selected moduli for blood vessel formation from human umbilical vein endothelial cells (ECs). Beamish et al (2019) engineered another PEG-based hydrogel with MMP-sensitive crosslinkers for capillary morphogenesis from encapsulated ECs. These studies have revealed that with a suitable stiffness, the robust in vitro vascular bed could be engineered in the synthetic elastic hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…All reagents were obtained from Thermo Fisher Scientific (Waltham, MA) unless specified. Endothelial and stromal cell sources in this study were chosen to provide continuity with our prior work [5,19]. Human umbilical vein endothelial cells (ECs) were harvested from fresh umbilical cords (obtained from the University of Michigan's Mott's Children's Hospital via an IRB-exempt process, without any identifying information provided to the researchers) and cultured in fully supplemented Vasculife VEGF Endothelial Medium (Lifeline Cell Technology LLC, Frederick, MD) as previously described [24].…”
Section: Cell Culturementioning
confidence: 99%
“…Hydrogels were functionalized with CGRGDS peptide ("RGD", Genscript, Piscataway, NJ) and crosslinked with Ac-GCRDVPMS↓MRGGDRCG-NH2 ("VPMS", Genscript, cleavage site indicated by ↓), which contains an N-terminal acetylation and a C-terminal amidation. These peptides were chosen to provide continuity with our previous work [5]. All reagents were prepared in batches of single-use aliquots.…”
Section: Peg-vs Hydrogel Formationmentioning
confidence: 99%
See 1 more Smart Citation